Taxonomy and nomenclature of Kalanchoe ×laetivirens (Crassulaceae subfam. Kalanchooideae), a further invasive nothospecies from Madagascar - Smith, Gideon F. (Phytotaxa, 2020)
The status of Kalanchoe laetivirens (Crassulaceae subfam. Kalanchooideae), which was recently for the first time recorded as naturalised beyond its native Madagascar, is changed to that of nothospecies as evidence indicates that it is of hybrid origin. An amplified description is provided for K. ×laetivirens and the nothospecies is illustrated.